1997
DOI: 10.1016/s0735-1097(97)00331-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Prognostic Significance of Simultaneous Versus Independent Resolution of ST Segment Depression Relative to ST Segment Elevation During Acute Myocardial Infarction

Abstract: Continuous analysis of ST segment resolution identifies, among patients with AMI with concomitantly occurring ST segment elevation and depression, a subgroup with increased in-hospital mortality. The pathogenic mechanism of increased mortality is not currently known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 34 publications
3
5
1
Order By: Relevance
“…In line with previous studies, we could confirm that worsened and/or STD-R≤50% was an independent predictor of hard clinical events with incremental prognostic value beyond clinical risk factors and STR. Additionally, the follow-up time of 12 months in the present study is longer compared with most of the previously reported trials,5 6 highlighting the mid-term prognostic value of STD-R. Our study complements previous findings by demonstrating the pathophysiological link between incomplete STD-R with more severe myocardial damage and consequently worse clinical outcome.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In line with previous studies, we could confirm that worsened and/or STD-R≤50% was an independent predictor of hard clinical events with incremental prognostic value beyond clinical risk factors and STR. Additionally, the follow-up time of 12 months in the present study is longer compared with most of the previously reported trials,5 6 highlighting the mid-term prognostic value of STD-R. Our study complements previous findings by demonstrating the pathophysiological link between incomplete STD-R with more severe myocardial damage and consequently worse clinical outcome.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, most of these studies were performed in the pre-PCI era and they were hampered by small sample sizes and single-centre observations. Early fibrinolytic reperfusion studies revealed an incidence of incomplete STD-R of approximately 15% 5. According to the largest study to date using contemporary immediate PCI therapy as reperfusion strategy, one out of four patients with STEMI develops poor STD-R (defined as STD-R≤50%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,25,26,27 This study showed that STEMI without resolution of ST segment depression had higher rate of MACEs in 30 days after myocardial infarction compared to those with resolution in ST segment depression. This result is consistent with other study showing higher rate of in-hospital mortality in STEMI patients without resolution in ST segment depression, compared to those with resolution in ST segment depression 28 . Other studies proved that inferior STEMI with reciprocal ST segment depression has larger infarct area, compared to those without reciprocal ST segment depression 30 .…”
Section: Discussionsupporting
confidence: 93%
“…The accuracy of ST-segment resolution may be potentially affected by the fact that the presence of postprocedural ST-segment elevation, even though in the presence of complete resolution, may represent residual ischemia as a consequence of suboptimal reperfusion. Furthermore, despite the pathogenesis of concomitant STdepression in patients with STEMI is still a matter of debate ("reciprocal" image of ST segment elevation in the infarct zone [19,20] or more extensive infarction [21,22] or additional ischemia beyond the infarct zone [23,24], several studies have shown its prognostic impact in patient with STsegment elevation [25][26][27]. Thus, it is conceivable that the inclusion of ST-segment depression in the evaluation of myocardial perfusion would give more prognostic information in addition to only ST-segment elevation.…”
Section: Epicardial and Myocardial Reperfusion In Stemimentioning
confidence: 99%